Constructing pragmatist knowledge : education, philosophy and social emancipation - Hooley, Neil (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book highlights the philosophical and creative basis of knowledge co-production by all citizens regardless of socio-economic background in contrast with neoliberal ideology. Exploring beginning, transitional and theorised practices, the book is a memoir of the author's extensive personal and educational experience. Each topic is discussed in relation to a number of pragmatist themes that run throughout to illustrate how the process of dialectical emergence underpins and substantiates meaningful human living. Building on the work of American Pragmatism, this is a systematic and detailed reintroduction of pragmatism to educators worldwide for progressive educational change"--
Philosophy and democratic society -- Immersion in beach inquiries -- Thinking about science and the universe -- Activism and the Vietnam War -- Confusions of teaching and curriculum -- Teacher unionism, then and now -- Community participation in education -- Educational policy-making -- Respecting indigenous knowledge in the regular classroom -- Corruption of higher education -- Collapse of the political left -- Bricolage : closing the circle of practice-theorising.
OCLC-licensed vendor bibliographic record.
Keywords: Education -- Philosophy; Education -- Social aspects; Educational change; EDUCATION / General